Characterization of alternative plasticizers in poly(vinyl chloride) sheets for blood containers. Issue 4 (8th April 2015) - Haishima, Yuji; Kawakami, Tsuyoshi; Fukui, Chie; Tanoue, Akito; Yuba, Toshiyasu; Ozono, Satoru; Kumada, Hidehumi; Inoue, Kaoru; Morikawa, Tomomi; Takahashi, Miwa; Fujisawa, Ayano; Yamasaki, Kayo; et al.
Abstract : This study aimed to optimize the ratio of dioctyl 4‐cyclohexene‐1, 2‐dicarboxylate (DOTH) and di‐isononyl‐cyclohexane‐1, 2‐dicarboxylate (DINCH ® ) for use as plasticizers in poly(vinyl chloride) (PVC) sheets. We also evaluated the biological safety of DOTH for its potential to be part of a safe PVC‐based blood container. The suppression of hemolysis in mannitol‐adenine‐phosphate / red cell concentrates (MAP/RCC) with DOTH/(DINCH ® ‐PVC) sheets and the elution of plasticizers from the sheets increased with higher DOTH compositions. The properties of the PVC sheet containing DOTH and DINCH ® in the ratio of 25:33 parts against PVC 100 parts as a weight were almost identical to the PVC sheet made of di(2‐ethylhexyl) phthalate. From a subchronic toxicity test, DOTH did not show any adverse effects on all organs, including the testes, epididymis, liver, and kidneys. The no‐observed‐adverse‐effect level was 300 mg/kg body weight/day in a rat. These results suggest that DOTH/DINCH ® (25:33) is a promising candidate for the replacement of di(2‐ethylhexyl) phthalate in blood containers. J. VINYL ADDIT. TECHNOL., 22:520–528, 2016. © 2015 Society of Plastics Engineers